Pharmacological Investigation on Ethanol Extract of Scindapsus hederaceus Miq. (Bangladesh Pharmaceutical Journal, 2017)
The present study was conducted to evaluate the antipyretic, anti-inflammatory and membrane stabilizing, antioxidant, thrombolytic, anti-diarrheal activities of Scindapsu shederaceus belonging to the Araceae family. In antipyretic test, temperature reduced from 101.53°F to 99.86°F (p